Comprehending Non-literal Language: Effects of Aging and Bilingualism - Sundaray, Shamala; Marinis, Theodoros; Bose, Arpita (Frontiers in Psychology, 2018)
A pressing issue that the 21st century is facing in many parts of the developed world is a rapidly aging population. Whilst several studies have looked at aging older adults and their language use in terms of vocabulary, syntax and sentence comprehension, few have focused on the comprehension of non-literal language (i.e. pragmatic inference-making) by aging older adults, and even fewer, if any, have explored the effects of bilingualism on pragmatic inferences of non-literal language by aging older bilinguals. Thus, the present study examined the effects of age(ing) and the effects of bilingualism on aging older adults’ ability to infer non-literal meaning. Four groups of participants made up of monolingual English-speaking and bilingual English-Tamil speaking young (17–23 years) and older (60– 83 years) adults were tested with pragmatic tasks that included non-conventional indirect requests, conversational implicatures, conventional metaphors and novel metaphors for both accuracy and efficiency in terms of response times. While the study did not find any significant difference between monolinguals and bilinguals on pragmatic inferences, there was a significant effect of age on one type of non-literal language tested: conventional metaphors. The effect of age was present only for the monolinguals with aging older monolinguals performing less well than the young monolinguals. Aging older bilingual adults were not affected by age whilst processing conventional metaphors. This suggests a bilingual advantage in pragmatic inferences of conventional metaphors.